2019
DOI: 10.1111/bph.14754
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of polycomb repressor complex 2 ameliorates neointimal hyperplasia by suppressing trimethylation of H3K27 in vascular smooth muscle cells

Abstract: Background and Purpose The increased proliferation and migration of vascular smooth muscle cells (VSMCs) after arterial injury contributes greatly to the pathogenesis of neointimal hyperplasia. As a major component of epigenetics, histone methylation plays an important role in several cardiovascular diseases. However, its role in restenosis is still unclear. Experimental Approach Human aortic VSMCs were challenged with PDGF‐BB, and total histones were extracted and analysed by HPLC/MS. For the in vivo study, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 42 publications
(55 reference statements)
4
15
0
1
Order By: Relevance
“…Since EZH2 is the primary methyltransferase that deposits H3K27me3 27 , the striking H3K27me3 upsurge due to angioplasty led us to investigate the underlying epigenetic regulations. As observed in our data 16 and recently reproduced by others 17,18 , pharmacological evidence implicated EZH2 as potentially important in neointima formation. Interestingly, both BRD4-and H3K27ac-associated ChIPseq peaks enriched at Ezh2, more in injured vs uninjured arteries ( Figure 2A).…”
Section: Brd4 and H3k27ac Enrich At The Ezh2 Gene In Injured Arteriessupporting
confidence: 92%
See 3 more Smart Citations
“…Since EZH2 is the primary methyltransferase that deposits H3K27me3 27 , the striking H3K27me3 upsurge due to angioplasty led us to investigate the underlying epigenetic regulations. As observed in our data 16 and recently reproduced by others 17,18 , pharmacological evidence implicated EZH2 as potentially important in neointima formation. Interestingly, both BRD4-and H3K27ac-associated ChIPseq peaks enriched at Ezh2, more in injured vs uninjured arteries ( Figure 2A).…”
Section: Brd4 and H3k27ac Enrich At The Ezh2 Gene In Injured Arteriessupporting
confidence: 92%
“…EZH2 recently emerged as a driver of cell state transitions such as cancer cell proliferation and migration, yet reports on EZH1 are limited and discrepant regarding its redundancy with EZH2 13,15 . Pharmacological evidence from our 16 and other groups 17,18 supports an IH-mitigating effect of pan-EZH1/2 inhibition, underscoring the importance of dissecting their functional roles and the mechanisms governing their expression levels. Moreover, BRD4 as an acetylation reader and EZH2 as a methylation writer are seemingly unrelated; their relationship has been overlooked 19 , especially in vascular pathogenesis.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…Angioplasty and coronary artery bypass grafting are highly effective treatment for narrowed coronary arteries due to atherosclerosis. However, restenosis resulting from neointima hyperplasia after angioplasty greatly dampens the satisfactory prognosis of the atherosclerosis for patients [59]. Recent research advances have indicated that histone methylation is critical for regulating neointima hyperplasia ( Fig.…”
Section: Histone Methylation In Atherosclerosis and Vascular Intimal mentioning
confidence: 99%